Quantitative Model for Reversibly Photoswitchable Sensors - Adelizzi, Beatrice (ACS Sens, 2021)
[Image: see text] Composed of a reversibly photoswitchable unit allosterically linked to a sensing module, reversibly photoswitchable sensors (rs-sensors) represent a new and attractive strategy to quantitatively read-out analyte concentrations. However, their kinetic response to illumination is complex, and much attention is required from the design to the application steps. Here, we exploit a generic kinetic model of rs-sensors which enables us to point to key thermokinetic parameters, such as dissociation constants and kinetic rates for exchange toward the analyte, and cross-sections for photoswitching. The application of the model allows to evaluate the robustness of the analyzed parameters and to introduce a methodology for their reliable use. Model and methodology have been experimentally tested on a newly reported calcium sensor based on a reversibly photoswitchable green fluorescent protein allosterically linked to a calcium-sensing module integrating calmodulin and an RS20 peptide.